2014
DOI: 10.1080/02602938.2014.921662
|View full text |Cite
|
Sign up to set email alerts
|

The impact on stakeholder confidence of increased transparency in the examination assessment process

Abstract: A group of postgraduate accounting and finance students were asked to participate in a three-phase exercise: sit an unseen past examination question; mark a fully anonymised previous student solution (exemplar); and then mark their own work. The marking process was facilitated by explaining and discussing the marking guide, assessment systems and process, and grade descriptors. Levels of marking accuracy significantly improved through the phases of the exercise, demonstrating a calibration of standards. Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Studies of university student perspectives support these concerns. Some students view transparency of assessment primarily as a means to get better marks and therefore explicit instructions lead to 'gaming' or instrumentalism rather than attainment (Norton 2004;Bamber 2015). Bell, Mladenovic, and Price (2013) found that half of their student sample thought of assessment materials as a 'recipe' book for achieving lecturer expectations.…”
Section: The Challenge Of Transparent Assessment Criteria: Views Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of university student perspectives support these concerns. Some students view transparency of assessment primarily as a means to get better marks and therefore explicit instructions lead to 'gaming' or instrumentalism rather than attainment (Norton 2004;Bamber 2015). Bell, Mladenovic, and Price (2013) found that half of their student sample thought of assessment materials as a 'recipe' book for achieving lecturer expectations.…”
Section: The Challenge Of Transparent Assessment Criteria: Views Frommentioning
confidence: 99%
“…From this perspective, students 'see through' to institutional expectations; they then grasp what they need to do to complete the task, including the basis for judging the quality of work (Jonsson 2014). At face value this seems reasonable and, when asked, students value transparency (Reddy and Andrade 2010;Bamber 2015). However transparent assessment criteria are surprisingly problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Transparency. Transparency in assessment has received increasing attention in higher education in recent years (Bamber, 2015;Bell et al, 2013;O'Donovan et al, 2004;Price, 2005). It refers to making the perceptions and expectations of assessors, including requirements, standards and assessment criteria, known and understood by all participants, particularly students (O'Donovan et al, 2004).…”
Section: Aims and Research Questionsmentioning
confidence: 99%
“…SETs are used for evaluating a teacher's teaching effectiveness, often by using questionnaires asking students to rate their perception of the course teacher. Regarding such discussions, there are many references (see, e.g., [1,46,47]), while other references are also seen ( [3,4,6,9,11,32,33,[35][36][37]).…”
Section: Introductionmentioning
confidence: 99%